2018
DOI: 10.1038/s41375-018-0197-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MYD88 and CXCR4 mutations in cell-free DNA of patients with IgM monoclonal gammopathies

Abstract: Liquid biopsyis being integrated into cancer diagnostics with profound therapeutic implications. However, its role in Waldenström’s Macroglobulinemia (WM) and IgM monoclonal gammopathies is still unclear. In this study, we evaluated the role of peripheral blood (PB) cell-free DNA (cfDNA) in characterizing the mutational status of MYD88 and CXCR4 of patients with IgM monoclonal gammopathies. Paired bone marrow (BM) tumor DNA (tDNA) and PB cfDNA samples from 98 patients (9 MGUS, 45 with WM in remission, 44 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 35 publications
2
38
1
Order By: Relevance
“…Unfortunately, the analysis of the genomic profile of CXCR4 is not routinely performed in clinics for LPL/WM patients. Importantly, the sensitivity of the used sequencing technique (allele-specific polymerase chain, Sanger, or whole-genome sequencing) and the nature of the analyzed sample (CD19-positive selected lymphocytes or whole BM) represent the most important issues in defining the mutational status of CXCR4 [153,172]. Therefore, universal guidelines are required to standardize the analysis and bring CXCR4 genomic profiling into clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the analysis of the genomic profile of CXCR4 is not routinely performed in clinics for LPL/WM patients. Importantly, the sensitivity of the used sequencing technique (allele-specific polymerase chain, Sanger, or whole-genome sequencing) and the nature of the analyzed sample (CD19-positive selected lymphocytes or whole BM) represent the most important issues in defining the mutational status of CXCR4 [153,172]. Therefore, universal guidelines are required to standardize the analysis and bring CXCR4 genomic profiling into clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, universal guidelines are required to standardize the analysis and bring CXCR4 genomic profiling into clinics. Interestingly, Bagratuni et al identified peripheral blood cell-free DNA as a useful, minimally invasive, cost-effective, and time-effective tool for the identification of the presence of both MYD88 and CXCR4 mutations in patients with IgM monoclonal gammopathies, avoiding unnecessary BM assessment [172].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Detection in peripheral blood using cell-free DNA is feasible, although with less sensitivity than in the BM. 13 MYD88 L265P detection is helpful to differentiate WM from morphologically similar lymphomas or IgM myeloma, but MYD88 L265P alone is not diagnostic of WM. Absence of MYD88 L265P does not exclude WM: 5% to 10% of patients with WM do not have MYD88 L265P (they have other MYD88 mutations 14 or have wild-type MYD88).…”
Section: Diagnosismentioning
confidence: 96%
“…Absence of MYD88 L265P does not exclude WM: 5% to 10% of patients with WM do not have MYD88 L265P (they have other MYD88 mutations 14 or have wild-type MYD88). MYD88 L265P also is found in 30% to 80% of IgM MGUS cases 10, 13,15 (depending on method's sensitivity) and in other lymphomas, but at significantly lower rates. In 20% to 40% of patients, lymphoplasmacytes have somatic activating mutations in the C-terminal domain of the C-X-C chemokine receptor type 4 (CXCR4) gene, 10, 16 which are similar to germline mutations observed in WHIM syndrome (CXCR4 WHIM ).…”
Section: Diagnosismentioning
confidence: 99%
“…Assessment of MYD88 and CXCR4 mutations are usually performed on bone marrow cells, according to hematological guidelines 11 . However, early experimental observations suggest that they could be evaluated also on peripheral blood cell or by using cell free DNA, with good sensibility and avoiding invasive diagnostic techniques 12,13 …”
Section: Signaling Pathways In B‐cell Malignanciesmentioning
confidence: 99%